Some properties of semi-simple splicing system over some permutation groups - Selvarajoo, Mathuri; Fong, Wan Heng; Sarmin, Nor Haniza; Turaev, Sherzod (2013)
The concept of splicing system was first introduced by Head in 1987 as a theoretical proposal for DNA based computation using the splicing operation – a formal model of the cutting and recombination of DNA molecules under the influence of restriction enzymes. Since splicing systems with finite sets of axioms and rules generate only regular languages, several restrictions in the use of rules have been considered, which increase the computational power of splicing systems. In this paper, we define a new variant of restricted variant of splicing systems, called semi-simple splicing systems controlled by permutation groups, and investigate the generative power of this variant.